(untitled) (Microbes and Health, 2016)
The present study was conducted for the determination of bacterial loads of ice cream. A total of nine samples of three brands-Igloo, Polar and Kwality were collected from local market from Dinajpur during the period from July to December, 2012. Thereafter, microbiological attribute were analyzed and studied comparatively. Total viable count (TVC), total Escherichia coli counts (TEC) and total Staphylococcal counts (TSC) were performed according to the American Public Health Association, using plate count agar medium for TVC and Eosin methylene blue (EMB) agar media for total E. coli count and Staphylococcus agar no. 110 for total Staphylococcal count. The average TVC counts/ml of Igloo, Polar and Kwality were 1.19 x 104 CFU/ml (log 4.1), 1.39 x 104 CFU/ml (log 4.1) and 8.53 x 103 CFU/ml (log 3.9) respectively. It was found that the highest extent of microbial contamination and proliferation of viable bacteria occurred in Polar ice cream The average E. coli counts obtained from the study was in Igloo 9.26 x 103 CFU/ml (log 4.0), in Polar 1.14 x 103 CFU/ml (log 3.0) and in Kwality 7.95 x 102 CFU/ml (log 2.9). The presence of numbers of E. coli in Igloo ice cream was little bit high indicated the poor hygienic practices during manufacture, post process contamination and unsatisfactory transportation. Statistically the E. coli were more closely related to total viable counts than the Staphylococcal counts. The average Staphylococcal counts in the samples of Igloo, Polar and Kwality were 2.60 x 103 CFU/ml (log 3.4), 0.0 CFU/ml (log 0.0), and 0.0 CFU/ml (log 0.0), respectively. The results demonstrated that kwality ice creams are of the superior quality product in respect of sanitary condition.